2010
DOI: 10.1007/s10096-010-0895-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of rotaviruses in Bulgaria: annual shift of the predominant genotype

Abstract: Rotavirus molecular epidemiology investigations provide important information about the incidence of rotavirus diseases and rotavirus strains in circulation in the prevaccine era. The purpose of this investigation was to study the burden of rotavirus disease, rotavirus strain diversity, and epidemiology specificities of rotavirus infections in Bulgaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…In recent studies, it was calculated that the rotaviruses cause approximately 111 million episodes of the gastroenteritis requiring only home care, 25 million clinical visits, 2 million hospitalizations and 352,000-592,000 deaths in children aged <5 years old worldwide, each year (Parashar et al, 2003). The frequency of rotavirus detection in this study (27.85%) was in keeping with numerous other studies conducted in developing and developed countries that have reported rotavirus to be responsible for between 14 and 50% of all cases of gastroenteritis (Nelson et al, 2008;Lacroix et al, 2010;Mladenova et al, 2010;Jere et al, 2011;Lorrot et al, 2011). Extensive molecular epidemiological studies globally have indicated that G1 is the most common circulating genotype.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In recent studies, it was calculated that the rotaviruses cause approximately 111 million episodes of the gastroenteritis requiring only home care, 25 million clinical visits, 2 million hospitalizations and 352,000-592,000 deaths in children aged <5 years old worldwide, each year (Parashar et al, 2003). The frequency of rotavirus detection in this study (27.85%) was in keeping with numerous other studies conducted in developing and developed countries that have reported rotavirus to be responsible for between 14 and 50% of all cases of gastroenteritis (Nelson et al, 2008;Lacroix et al, 2010;Mladenova et al, 2010;Jere et al, 2011;Lorrot et al, 2011). Extensive molecular epidemiological studies globally have indicated that G1 is the most common circulating genotype.…”
Section: Discussionsupporting
confidence: 78%
“…Because of the appearance of unusual rotavirus strains such as G10, G12 from South Korea (Le et al, 2008), Italy (Zuccotti et al, 2010), France (De Rougemont et al, 2011) and other countries (Pun et al, 2007;Annarita et al, 2010), in this research were used from the specific primers them for the first time in Iran, but none of them were observed in this study. Overall, 79.54% of hospitalizations due to rotavirus gastroenteritis occurred in children younger than 2 years more than in the older age groups, as was found in previous investigations in various countries (Khalili et al, 2004;Pun et al, 2007;Lacroix et al, 2010;Mladenova et al, 2010). The high frequency of rotavirus infection in this age group has important implications for the consideration of strategies for prevention through the routine immunization of children less than 2 years of old.…”
Section: Discussionsupporting
confidence: 54%
“…However, a peak of infection was observed between January until March. 33 Variation in proportion of RVGE over time. Examining changes in rotavirus infection over time was possible for four countries, Albania, Bulgaria, Russia and Poland (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…19,28 The remaining countries report a percentage of rotaviral infection of between 32% and 43%. [15][16][17]19,[21][22][23][24][25][26][27][28][29][30][31]33 A number of countries reported seasonality data ( Table 1). For most countries in Central and eastern Europe the season for RVGE is in the winter months from November to May with a peak between March and May.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation